Introduction to the Special Issue of the 55th Anniversary of Urban and Regional Planning Education: Inclusive Urban Development in the Decentralization Era - Elkana Catur Hardiansah (Journal of Regional and City Planning, 2015)
[Tanpa Abstrak]. Ini adalah pengantar Edisi Khusus "Pembangunan Kota Inklusif di Era Desentralisasi".[No abstract]. This is an introduction to the Special Issue "Inclusive Urban Development in the Decentralization Era".